Covalent Bond Scission in the Mullins Effect of a Filled Elastomer: Real‐Time Visualization with Mechanoluminescence. (5th August 2016) - Clough, Jess M.; Creton, Costantino; Craig, Stephen L.; Sijbesma, Rint P.
Abstract : Strain‐induced light emission from mechanoluminescent cross‐linkers in silica‐filled poly(dimethylsiloxane) demonstrates that covalent bond scission contributes significantly to irreversible stress‐softening upon the initial extension, known as the Mullins effect. The cross‐linkers contain dioxetanes that emit light upon force‐induced bond scission. The filled elastomer emits light in cyclic uniaxial tension, but only on exceeding the previous maximum strain. The amount of light increases with hysteresis energy in a power law of exponent 2.0, demonstrating that covalent bond scission becomes increasingly important in the strain regime studied. Below 100%–120% strain, corresponding to energy absorption of (0.082 ± 0.012) J cm −3, mechanoluminescence is not detectable. Calibration of the light intensity indicates that by 190% strain, less than 0.1% of the dioxetane moieties break. Small but significant amounts of light are emitted upon unloading, suggesting a complex stress transfer to the dioxetanes mediated by the fillers. Pre‐strained material emits light on straining perpendicularly, but not parallel to the original tensile direction, demonstrating that covalent bond scission is highly anisotropic. These findings show that the scission of even a small number of covalent bonds plays a discernible role in the Mullins effect in filled silicone elastomers. Such mechanisms may be active in other types of filled elastomers. Abstract : Applying cycles of tensile strain to silica‐filled poly(dimethylsiloxane) functionalized with 1, 2‐dioxetanes leads to the emission of mechanically induced chemiluminescence as covalent bonds break in the material. Monitoring in real time, light emission is observed predominantly on the first cycle to a strain. Covalent bond scission is shown conclusively to contribute to Mullins stress‐softening and to exhibit strong anisotropy.